Mechanical Properties of High Entropy Alloy Nanoparticles Obtained by Nanoindentation: A Bcc Hfnbzrtati and Fcc Fenicrcocu Case - Valencia, F (Elsevier Ltd, 2025)
Atomistic simulations were employed to investigate the mechanical properties of a Face-centered Cubic (FCC) FeNiCrCoCu and a base centered cubic (BCC) HfNbTaZrTi High Entropy Alloy (HEA) nanoparticles. The study reveals that both types of nanoparticles exhibit significantly higher yield strength, compressive strength, and effective Young s modulus compared to their bulk HEA counterparts, consistent with experimental observations. Plastic deformation in BCC nanoparticles is facilitated by 1/2〈111〉 dislocations, serving as precursors for twin-assisted deformation. In contrast, FCC nanoparticles undergo plastic deformation characterized by nucleation and pile-up of stacking faults, akin to other FCC nanoparticles. Results are compared to the respective average atom materials. For FCC AA the behavior is extremely similar to the HEA FCC case. For BCC AA there are significant differences in dislocation and twinning behavior compared to the BCC HEA case, leading to more twins and less dislocations in the AA case. The similarity in deformation mechanisms for HEA and FCC nanoparticles suggests that the crystal lattice dictates deformation behavior, rather than chemical complexity. However, for BCC NPs, chemical complexity plays a role in the interplay between dislocations and twins, and on dislocation evolution. This study enhances our understanding of high-entropy alloy nanoparticle mechanics and offers insights into tailoring material responses through surface modification. © 2025 Elsevier Ltd